Moderation Model For Determinants Of Residential Location Choice And Residential Location In Peri-Urban Areas Of Seberang Perai Penang - Mukhtar, Syafiqah Nazurah (2022)
Residential location choice involves making a decision on the location of available housing real estate for people to live in. There is limited research specifically investigating the factors that influence residential location choice especially in peri-urban areas. The relationships between factors are also more complex, resulting in inconsistency and trade-off effect. This study aims to examine the strength and significance of determinants of residential location choice and develop a moderation model to understand further the complexity of relationships and the trade-off effect. Due to the nature of this research, this study adopted quantitative research approach and used questionnaire survey for data collection.